2022
DOI: 10.3389/fpsyt.2022.922272
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Functional Connectivity of the Orbitofrontal Cortex Is Associated With Excited Symptoms in First-Episode Drug-Naïve Patients With Schizophrenia

Abstract: BackgroundSchizophrenia (SZ) is associated with the highest disability rate among serious mental disorders. Excited symptoms are the core symptoms of SZ, which appear in the early stage, followed by other stages of the disease subsequently. These symptoms are destructive and more prone to violent attacks, posing a serious economic burden to the society. Abnormal spontaneous activity in the orbitofrontal cortex had been reported to be associated with excited symptoms in patients with SZ. However, whether the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…In this context, we found only two previous works reporting a change in the FC of the OFC to an area of the postcentral gyrus: Research on children with externalizing disorders found that adolescents with a positive family history of substance use disorders had a stronger negative FC between the left lateral OFC and the right postcentral gyrus [77]. Another study reported a decreased FC of the left OFC to several areas of the (bilateral) postcentral gyrus in patients with schizophrenia [57]. While this again points towards the relevance of that connection in psychiatric disorders, there is not enough evidence to make further assumptions.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In this context, we found only two previous works reporting a change in the FC of the OFC to an area of the postcentral gyrus: Research on children with externalizing disorders found that adolescents with a positive family history of substance use disorders had a stronger negative FC between the left lateral OFC and the right postcentral gyrus [77]. Another study reported a decreased FC of the left OFC to several areas of the (bilateral) postcentral gyrus in patients with schizophrenia [57]. While this again points towards the relevance of that connection in psychiatric disorders, there is not enough evidence to make further assumptions.…”
Section: Discussionmentioning
confidence: 67%
“…Based on a detailed parcellation of the OFC by Kahnt et al [11], small spherical regions of interest (ROIs) around the reported center coordinates (Table 1) were generated. As some studies reported differential functions of the left and right OFC [57,58], seeds were created separately for the left and right hemispheres (see Figure 1). We chose a radius of 4 mm, as a 5 mm radius resulted in multiple voxels overlapping and, therefore, being unsuitable for a differential analysis, although the smaller 4 mm was still sufficiently large for our data.…”
Section: Seed-to-whole-brain Analysismentioning
confidence: 99%
“…In Cheon's study, negative symptom scores showed predominantly stronger positive associations with ALFF in the temporal and frontal brain regions [77]. However, Chen's research demonstrated that OFC-related re-fc was negatively correlated with excited symptoms in first-episode patients with SZ [78]. Therefore, further evidence on the relationship between spontaneous brain activity and clinical symptoms in SZ patients is required for consensus.…”
Section: The Correlation Between Alff Falff Reho Rs-fc and Symptom Se...mentioning
confidence: 96%
“…Second, spontaneous brain activity was evaluated via fALFF in the context of functional segregation. Although this approach has been applied as a reliable method of localizing brain regions in relation to personality/behavioral traits [23,24], future studies should combine the functional connectivity approach with fALFF to gain further insights into the network context [63]. In addition, studies repeatedly reported that gray matter density and white matter integrity were associated with individual differences in various types of social cognitive abilities in healthy subjects and clinical populations [64][65][66][67].…”
Section: Plos Onementioning
confidence: 99%